Expectation of reward differentially modulates executive inhibition (2019)
Background: Inhibitory control, a key modulatory component of cognition guiding strategy and behaviour, can be affected by diverse contingencies. We explore here the effect of expectation of reward over behavioural adjustment in a Stop Signal Task modulated by reward. We hypothesize that cognitive control is modulated by different expectation of the reward. Methods: Participants were allocated to two groups differing in their degree of knowledge in what to expect from rewards. Expected Specific Reward participants (N = 21) were informed of the different monetary feedbacks they would receive after each successful inhibition. Unexpected Reward participants (N = 24) were only told that they would receive monetary reward after correct inhibitory trials, but not the amounts or differences. Results: Our results confirmed previous observations demonstrating a "kick-start effect" where a high reward feedback at the beginning of the task increases response inhibition. The Expected Specific Reward condition seems also to improve inhibitory control -as measured by the stop signal reaction time (SSRT)-, compared to the Unexpected Reward group. Conclusions: Knowledge of reward magnitudes seems to play a role in cognitive control irrespective of feedback magnitude. The manipulation of reward expectation appears to trigger different strategies for cognitive control, inducing a bottom-up effect of external cues, or a top-down effect given by the anticipation of incoming rewards. This is an early exploration to unearth possible higher order modulators - expectation and motivation- of cognitive control. This approach aims to gain insight into diverse psychopathological conditions related to impulsivity and altered reward systems such as Attention Deficit Hyperactive Disorder (ADHD), personality disorders, substance abuse, pathological gambling and cognitive aspects of Parkinson Disease.